2015
DOI: 10.1016/j.cell.2014.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Human Immune System Is Largely Driven by Non-Heritable Influences

Abstract: SUMMARY There is considerable heterogeneity in immunological parameters between individuals, but its sources are largely unknown. To assess the relative contribution of heritable versus non-heritable factors, we have performed a systems-level analysis of 210 healthy twins between 8–82 years of age. We measured 204 different parameters, including cell population frequencies, cytokine responses, and serum proteins, and found that 77% of these are dominated (> 50% of variance) and 58% almost completely determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

50
849
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 902 publications
(908 citation statements)
references
References 50 publications
50
849
1
8
Order By: Relevance
“…This evolutionary raison d'être of adaptive immunity explains its dependence on so few genes, germline mutations of which underlie B-and/or T-cell deficiencies with a broad and lethal infectious phenotype. Consistently, a recent twin study showed that adaptive immunity parameters diverge much more rapidly with age than do other hematological parameters in identical twins (134,135). The somatic (as opposed to germline) failure of adaptive responses, whether genetic or epigenetic, may account for a proportion of primary infections.…”
Section: A Genetic Theory Of Infectious Diseases: Challenges Aheadmentioning
confidence: 60%
“…This evolutionary raison d'être of adaptive immunity explains its dependence on so few genes, germline mutations of which underlie B-and/or T-cell deficiencies with a broad and lethal infectious phenotype. Consistently, a recent twin study showed that adaptive immunity parameters diverge much more rapidly with age than do other hematological parameters in identical twins (134,135). The somatic (as opposed to germline) failure of adaptive responses, whether genetic or epigenetic, may account for a proportion of primary infections.…”
Section: A Genetic Theory Of Infectious Diseases: Challenges Aheadmentioning
confidence: 60%
“…Brodin et al (2015) recently completed a systemic study of heritability of immune cell traits in a large cohort of twins, and concluded that while most traits are not heritable, some are highly heritable [30]. These include CD56, CD4 and CD8 populations, tagged by these and other CD markers.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that the environment shapes the human immune system and accounts for its heterogeneity among individuals [13]. The oral, gut, and skin microbiotas could play a key role in the pathogenesis of systemic and organ-specific autoimmune diseases [14].…”
mentioning
confidence: 99%